Kewenangan dan Mekanisme Penyelesaian Sengketa Perbankan dalam Rangka Perlindungan Nasabah Perbankan Setelah Dibentuknya Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan - Imam Asfali (Inovasi Pratama Internasional. Ltd, 2023)
The absence of balanced protection puts customers in a weak position. This aspect of customer protection can also be seen in the national banking business. There are two dominant problems that are often complained of by customers of banking services. First, complaints about banking products such as ATMs (Automatic Teller Machines), credit cards, and various types of savings accounts. Also included in complaints about banking products are promises of prizes and advertisements for banking products. Second, complaints about the unsympathetic and unprofessional work of officers, especially service point officers such as tellers, customer service, and security guards. From these problems it can be seen that the aspect of customer protection is a very important aspect to pay attention to and not to be violated. This type of research is normative juridical, namely by examining library materials and secondary materials. Data sources in this study are secondary data. The data collection technique used in this research is through library research techniques. Banking dispute resolution mechanisms in the context of protecting banking customers, namely Dispute Resolution through OJK in implementing dispute resolution facilities, OJK appoints facilitators who are OJK officers in the field of Consumer Education and Protection, OJK Consumer Services Directorate. OJK's authorities in the context of consumer protection, especially banking customer protection, are as follows: (a) To provide information and education to the public on the characteristics of the financial services sector, its services and products; (b) Asking financial service institutions to stop their activities if these activities have the potential to harm society; and (c) Other actions deemed necessary in accordance with the provisions of laws and regulations in the financial services sector. The impact of the enactment of Law Number 21 concerning the Financial Services Authority on banking customers is that the Financial Services Authority is able to carry out the banking supervisory function. Moreover, this has been mandated in Law Number 21 of 2011.